Accute malnutrition and visceral failure. - Bertullo, Hugo; Muguruza, Alvaro (Cirugía del Uruguay, 1988)
A prospective study was carried out in order to determine the existence or not of a connection between acule malnutrition and visceral failure in multi-aggressed patients, Starting out with two comparable groups, group A, suffering from more aggressions, showed a consisten! loss of nitrogen which was greater !han the intake, (nitrogen balance becoming positiva only in 43% of the cases. Visceral failure was statistically greater in this group; it was also directly related to nitrogen loss, and this showed, as a conclusion, that the aforementioned connection exists.